Inside Cover: Room Temperature Hydrogen Production from Ethanol over CeNiXHZOY Nano‐Oxyhydride Catalysts (ChemCatChem 8/2013). Issue 8 (25th July 2013) - Fang, Wenhao; Pirez, Cyril; Paul, Sébastien; Capron, Mickaël; Jobic, Hervé; Dumeignil, Franck; Jalowiecki‐Duhamel, Louise
<x xml:space="preserve">Abstract</x> Taking alcohol from the nanobar The cover picture shows the use of nickel and cerium nano‐oxyhydride catalysts in hydrogen production from ethanol in the presence of water and oxygen. In their Full Paper on p. 2207 ff., L. Jalowiecki‐Duhamel et al. describe the characterization and catalytic properties of the nano‐compounds. Hydrogen production (45 mol %) and total conversion of ethanol remain almost constant over at least 75 h time‐on‐stream with only a small energy input (reaction in oven at 60 °C), thanks to the presence of hydride species stored in the solid.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>